(untitled) (Repertorio Científico, 2022)
Introduction: Climate change and environmental pollution have made access to quality drinking water for human consumption and use increasingly difficult. Fog catchers are an alternative way of capturing water in the natural environment for different needs, and in turn allow quantifying the potential that horizontal rain has as a contribution to the water cycle. Objective: To quantify the water supply produced by horizontal rain, in Cerro Trinidad, San Marcos de Tarrazú, San José, Costa Rica, from July to September 2021. Methods: By constructing 2 artificial collectors (rectangular in shape, six square meters, six meters high), the water contribution generated by horizontal rain displacement is captured. The incidence of altitude and plant structures allow the presence of mist on the Trinidad hill, the placement of fog catchers in its highest parts is an alternative to reduce the water footprint of the community of San Marcos de Tarrazú. Results: The results obtained show a total of about 712 liters of water capture, in about 1276 net hours with the presence of fog, that is, an average of 53 effective days of horizontal rain probability during the study period. Conclusions: With an affordable trend of atmospheric water uptake of 13 liters per day in a catchment area of 12 m2 of saran, which in proportion to the forest cover of Cerro Trinidad, is equivalent to a water contribution of at least 188,320 liters per hectare in the area altitude influence between 1700 meters above sea level and 1900 meters above sea level on the Cerro Trinidad in San Marcos de Tarrazú. Key words: Horizontal Rain, Hidden Rain, Mist, Fog Catcher, Climate chance, PROLAB